Domus Aurea in-Visible: from research to fruition (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
This contribution intends to present the study and cataloguing activities of the artefacts found in the Domus Aurea. It is an initiative that is part of a more general project of the Parco archeologico del Colosseo, aimed, first of all, at recontextualising the artefacts preserved in the deposits. The project, in its initial phase, concerned the study and analysis of the marble fragments found in the Domus Aurea with the aim in the first instance of recovering what remains of the sumptuous sculptures and architectural decorations that must have adorned Nero's palace. “Digging” in the deposits, a refined Corinthian-type column capital in Proconnesian marble was found, recently restored and which, together with some sculptures, also pertaining to the Domus Aurea, has been placed along the renewed tour route. The capital is part of the group with lyre motif, which, from the Augustan age onwards, spread widely in Rome and was part of the vast production destined to satisfy the ostentatious luxury requirements of aristocratic and imperial patrons. It is also of particular interest that we know the details of its discovery and a certain chronological indication, as it is consistent with the period of construction of the Domus Aurea (64-68 AD).
Keywords: Domus Aurea; Nero; capital; proconnesian; acanthus; seashell